2015
DOI: 10.1089/ten.tea.2013.0779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polycaprolactone-Based Scaffolds on the Blood–Brain Barrier and Cerebral Inflammation

Abstract: Severe pathoanatomical and mechanical injuries compromise patient recovery and survival following penetrating brain injury (PBI). The realization that the blood-brain barrier (BBB) plays a major role in dictating post-PBI events has led to rising interests in possible therapeutic interventions through the BBB. Recently, the choroid plexus has also been suggested as a potential therapeutic target. The use of biocompatible scaffolds for the delivery of therapeutic agents, but little is known about their interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…PCL had already been shown to be permissive to neural growth. In vitro, neural cells grow over the surface of 2D films made of PCL and show a normal electrophysiologic activity . PCL has seldom been used in vivo in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…PCL had already been shown to be permissive to neural growth. In vitro, neural cells grow over the surface of 2D films made of PCL and show a normal electrophysiologic activity . PCL has seldom been used in vivo in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…According the investigations of neurogenic potential and neurons, it was demonstrated that PCL did not evoke an undesirable inflammatory response [ 69 ]. Moreover, PCL-based scaffolds did not cause further changes to the vascular supply in and around the defect region [ 70 ]. In our study, we could also observe a high tolerance of PCL devices by host tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Coronal paraffin wax brain tissue sections were obtained as previously described 21 . In order to measure the apoptosis of hippocampal neurons, In Situ Cell Death Detection Kit (Roche, Switzerland) was used according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis of hippocampal neurons after resuscitation was detected by terminal deoxynucleotidyl transferase-mediated uridine 59-triphosphate-biotin nick end labeling (Tunel) assay. Coronal paraffin wax brain tissue sections were obtained as previously described 21 . In order to measure the apoptosis of hippocampal neurons, In Situ Cell Death Detection Kit (Roche, Switzerland) was used according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%